Synovial Lipomatosis of the Glenohumeral Joint - Shaul Beyth; Ori Safran (Case Reports in Orthopedics)
Synovial lipomatosis (also known as lipoma arborescens) is a rare and benign lesion affecting synovium-lined cavities. It is characterized by hyperplasia of mature fat tissue in the subsynovial layer. Although the most commonly affected site is the knee joint, rarely additional locations such as tendon sheath and other joints are involved. We present a case of synovial lipomatosis of the glenohumeral joint in a 44-year-old man. The clinical data radiological studies and histopathologic results are described, as well as a review of the current literature.